Policy Implementation of Street Children Development Program in Medan City (Study of Medan City Social Office) - Ratna Sari Dewi; Elazhari Elazhari; Mariance Manao (LEGAL BRIEF, 2022)
The activities of street children in the city of Medan are diverse, including as buskers, cigarette traders, newspaper traders, and so on. This is the main duty of the government to street children. The aim of the study was to determine the implementation of street children development program policies at the Medan City Social Service and street children development program policies. This research method is a qualitative method. Data collection techniques using observation and interviews. The results of the research on the implementation of street children development program policies at the Medan City Social Service have not been maximized in terms of the street children that we still find at crossroads or at red lights and crossroads. The policy of the Medan City Social Service in implementing street children development programs, namely control and outreach programs and skills training. The obstacle faced is that street children who have been returned to their families still like to return to the streets, so that the government's program to respect the city in the absence of street children at crossroads cannot be implemented. The government and the Medan City Social Service can only reduce the number of children on the streets. For this reason, it is suggested that there should be more programs to improve children's skills and socialization.